2018
DOI: 10.1175/mwr-d-17-0254.1
|View full text |Cite
|
Sign up to set email alerts
|

Important Factors for Tornadogenesis as Revealed by High-Resolution Ensemble Forecasts of the Tsukuba Supercell Tornado of 6 May 2012 in Japan

Abstract: To identify important factors for supercell tornadogenesis, 33-member ensemble forecasts of the supercell tornado that struck the city of Tsukuba, Japan, on 6 May 2012 were conducted using a mesoscale numerical model with a 50-m horizontal grid. Based on the ensemble forecasts, the sources of the rotation of simulated tornadoes and the relationship between tornadogenesis and mesoscale environmental processes near the tornado were analyzed. Circulation analyses of near-surface, tornadolike vortices simulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 51 publications
4
35
0
Order By: Relevance
“…Finally, we note that the 50-m ensemble dataset produced in this study could be used for diagnostic analyses aimed at better understanding tornadogenesis dynamics, as was done in the most recent study of Yokota et al (2018) for their ensemble forecasts at 50-m grid spacing of tornadoes occurring within a supercell storm over Japan. In future work, we plan to perform diagnostic analyses on the ensemble simulations for the understanding of tornadogenesis dynamics, following the approaches of Yokota et al (2018) and other recent dynamical studies of tornadoes and tornadogenesis processes (e.g., Schenkman et al 2014;Dawson et al 2016;Roberts et al 2016;Roberts and Xue 2017). Other possible future work using this dataset will include using the vortex wind analysis method of Q.…”
Section: Summary and Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Finally, we note that the 50-m ensemble dataset produced in this study could be used for diagnostic analyses aimed at better understanding tornadogenesis dynamics, as was done in the most recent study of Yokota et al (2018) for their ensemble forecasts at 50-m grid spacing of tornadoes occurring within a supercell storm over Japan. In future work, we plan to perform diagnostic analyses on the ensemble simulations for the understanding of tornadogenesis dynamics, following the approaches of Yokota et al (2018) and other recent dynamical studies of tornadoes and tornadogenesis processes (e.g., Schenkman et al 2014;Dawson et al 2016;Roberts et al 2016;Roberts and Xue 2017). Other possible future work using this dataset will include using the vortex wind analysis method of Q.…”
Section: Summary and Discussionmentioning
confidence: 93%
“…We also note that, because the 500-m run cannot explicitly resolve tornadoes, there appears not to be a direct relation between the simulated tornado on the 50-m grid and the simulated supercell characteristics on the 500-m grid. Investigating which aspects of the parent storm determine the characteristics of embedded tornado is a separate research question related to both tornado dynamics and predictability; for example, Coffer et al (2017) and Yokota et al (2018) found that the vertical perturbed pressure gradient force resulting from the mesocyclone to be vital for tornadogenesis, and Roberts and Xue (2017) found that the ingestion of frictionally generated vorticity into the low-level mesocyclone led to lowering of the mesocyclone circulation and the creation of a strong upward pressure gradient force, ultimately contributing to tornadogenesis. Investigating these topics will require a separate study.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis of the videos presented in Figure 5 also shows that the observed vortices in the Tuscaloosa tornado (as well as other tornado events, e.g., [7][8][9]) consistently display the same behavior. This suggests that HVs near the surface have horizontal vorticity vectors that point to the left of the horizontal wind vector at large angles, implying considerable crosswise horizontal vorticity [11,13,14,52]. This can be seen in Figure 8a, which shows the horizontal vorticity field at 1 m and 158 m AGL.…”
Section: Near-ground Flow Kinematics and Potential Hv Formation Mechamentioning
confidence: 87%